ANALISIS PENGEMBANGAN KAWASAN WISATA ALAM AIR TERJUN TAHAPAN TELU BERDASARKAN POTENSI BIOFISIK - Fernando P Londong; Fabiola B. Saroinsong; Maria Y. M. A. Sumakud (Sam Ratulangi University, 2021)
This study aims to analyze the biophysical potential of the Kali Tahapan Telu Waterfall area. The research was conducted in August 2020 at Kali Tahapan Telu Waterfall, Kali Village, Pineleng District, North Sulawesi. This study uses a survey method for primary data collection, namely by conducting interviews with parties related to the management of this natural tourism area, as well as direct observation in the tourist area of Kali Tahapan Telu Waterfall and the surrounding environment on aspects of tourist attraction, accessibility, accommodation, and facilities. and tourism support infrastructure. Secondary data were obtained from existing references and agencies. Data analysis used in this study was the scoring technique. The results showed that this natural tourism area has biophysical potential which is the ability, strength of the biotic and physical environment that the area has which allows it to be developed into. The attraction for visitors to come and enjoy this tourist area is as follows. The tourist area of Kali Tahapan Telu Waterfall has 2 (two) types of fauna that are endemic to North Sulawesi and 4 (four) types of flora that characterize the North Sulawesi area. In addition, there are several good views towards the outside of the tourist attraction and an attractive good view between parts of the tourist attraction. Based on the results of the biophysical potential analysis using the scoring technique, it was found that the results of the biophysical potential of Kali Tahapan Telu Waterfall were in the medium category. The development of biophysical potential can be done by planting several types of endemic plants in and around tourist areas to increase attractiveness by increasing the diversity of natural resources that can be enjoyed, especially endemic species that have characteristics in tourist areas while carrying out conservation efforts, as well as being a vehicle for education about sources. local power. In addition, the development of biophysical potential can also be done by adding infrastructure in the form of viewing posts or gazebo with local architectural, as well as attractive landscape designs to add beauty and support the potential view. Regarding the increase in the use value of agricultural land indirectly, the existence of community agricultural land around the area planted with plants that have regional characteristics of North Sulawesi, namely cloves, coconut, palm and nutmeg are utilized and supported by landscape designs in natural tourism areas that frame and strengthen the scenery so that it adds to tourist attraction. In addition, the increase in the use value of agricultural land is directly and simultaneously in line with community empowerment, namely the processing of parts of community agricultural land products that are not traded to be developed into souvenirs which have not been provided until now. Community empowerment is also carried out by involving the surrounding community in increasing tourist attractions, namely by tourist attractions, especially regional cultural attractions.